Elevated Serum Interleukin-23 Levels in Patients with Oral and Cutaneous Lichen Planus - Maryam Mardani; Hossein Mofidi; Ladan Dastgheib; Sara Ranjbar; Nasrin Hamidizadeh (Mediators of Inflammation)
Lichen planus is considered a chronic inflammatory disease which affects different sites, such as the skin, mucous membranes, hair, and nails. Based on the evidence, a complex cytokine network plays a crucial role in lichen planus pathogenesis. The study was aimed at assessing the serum IL-23 levels in the patients with cutaneous and oral lichen planus compared to healthy controls. Method. The study included 30 cutaneous lichen planus patients, 20 oral lichen planus patients, and 33 control subjects. Five milliliters of peripheral blood was obtained from each patient, and the serum was separated. IL-23 levels were determined using the ELISA kit, and the data were analyzed using the Mann–Whitney test. Results. IL-23 levels in the patient serum with oral lichen planus (P value ≤ 0.001) were significantly higher than in controls. Furthermore, there were significant differences in IL-23 serum levels in the patients with cutaneous lichen planus compared to the healthy controls (P value ≤ 0.001). Moreover, IL-23 serum levels were statistically different between patients with cutaneous lichen planus and patients with oral lichen planus (P value ≤ 0.001). Based on the mean concentration of interleukin-23, IL-23 levels were higher in the patients with oral lichen planus than in the patients with cutaneous lichen planus. Conclusions. Elevated serum IL-23 levels in the patients with oral lichen planus may indicate that IL-23 plays a crucial role in the pathogenesis of oral lichen planus. However, more research is needed with a larger sample size.